Developing E-Comic Learning Media for Indonesian Language to Enhance Fifth-Grade Students' Learning Interest - Indri Yani; Siti Rifdah Triana; Meizura Ansi Hidayatunnisa; Aqilla Salsabila (Journal of General Education and Humanities, 2025)
This study aims to develop e-comic learning media for teaching imperative sentences in fifth-grade Indonesian language classes. Employing the Research and Development (R&D) method based on the ADDIE model, the development process includes stages such as analysis, design, development, implementation, and evaluation. The resulting product underwent expert validation, receiving feasibility scores of 89.23% from media experts and 92.30% from language experts, both of which were categorised as “very feasible.” A limited trial was conducted with 29 fifth-grade students, yielding a positive response rate of 81.10%. The e-comic media integrates visual, interactive, and narrative elements tailored to the characteristics of the digital native generation, thereby increasing students’ learning interest and engagement. The findings indicate that e-comic media is not only highly feasible but also effective in enhancing learning motivation and participation in Indonesian language lessons. This media provides a practical and innovative solution for addressing the need for engaging instructional tools in primary education, supporting educators in optimising the learning experience for young students.